2019
DOI: 10.3390/ijms20163877
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisomes in Immune Response and Inflammation

Abstract: The immune response is essential to protect organisms from infection and an altered self. An organism’s overall metabolic status is now recognized as an important and long-overlooked mediator of immunity and has spurred new explorations of immune-related metabolic abnormalities. Peroxisomes are essential metabolic organelles with a central role in the synthesis and turnover of complex lipids and reactive species. Peroxisomes have recently been identified as pivotal regulators of immune functions and inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 164 publications
(213 reference statements)
4
89
0
2
Order By: Relevance
“…The genes were applied to enrichment analysis and they were significant enriched in 11 terms (Figure 8B). Interestingly, except peroxisome, several immune-related processes including phagocytosis, regulation of adaptive immune response, regulation of lymphocyte mediated immunity, and ECM affiliated were enriched, consistent with the associations of peroxisomes with immune response and inflammation reported in previous studies (Vijayan et al, 2017;Di Cara et al, 2019), indicating the implication of HSD17B4, ACAA1, and PXMP4 in these processes.…”
Section: Nsclc Specific Network Of Hsd17b4 Acaa1 and Pxmp4 And Theisupporting
confidence: 88%
“…The genes were applied to enrichment analysis and they were significant enriched in 11 terms (Figure 8B). Interestingly, except peroxisome, several immune-related processes including phagocytosis, regulation of adaptive immune response, regulation of lymphocyte mediated immunity, and ECM affiliated were enriched, consistent with the associations of peroxisomes with immune response and inflammation reported in previous studies (Vijayan et al, 2017;Di Cara et al, 2019), indicating the implication of HSD17B4, ACAA1, and PXMP4 in these processes.…”
Section: Nsclc Specific Network Of Hsd17b4 Acaa1 and Pxmp4 And Theisupporting
confidence: 88%
“…The presence of HMGB1 in the peroxisomes strongly suggested that HMGB1 played another role in the functional regulation of cellular oxidative stress. Based on the specific localization of catalase, an H 2 O 2 -degrading enzyme, and other redox-related enzymes in peroxisomes, it has been speculated that peroxisomes are involved in the regulation of the redox state and a related intracellular signaling pathway [22,23]. Three cysteine residues on HMGB1 were reported to be sensitive to oxidative stress and to respectively form three kinds of molecular species: an all-thiol form, a disulfide form, and a sulfoxide form.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies will be needed to determine the molecular species of HMGB1 in the ischemic brain. In addition to the redox regulation, it has recently been suggested that peroxisomes function as pivotal regulators of immune functions and inflammation through immunometabolism [22]. It is worthy of mention that two HMGB1-localizing subcellular organelles, i.e., mitochondria and peroxisomes, might have a special interaction spatially and functionally [22,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peroxisomes are closely connected to the communication between mitochondria and ER through lipid and ROS metabolic pathways, essential metabolites and signals in cellular immune responses [ 175 , 176 , 177 ]. Polyunsaturated fatty acids (PUFAs) generated by peroxisomes are essential for the synthesis of pro-resolving mediators (e.g., resolvins) to the resolution of inflammation [ 178 , 179 ]. Peroxisomes can regulate cellular cholesterol homeostasis.…”
Section: Roles Of Molecular Chaperones In Metabolism and Immune Fumentioning
confidence: 99%